Family Empowerment In Patients With Severe Mental Disorders In Banjarmasin, Indonesia - Irmah Setia Waty; Setia Budhi; Andi Tenri Sompa (Wadah Inovasi Indonesia, 2021)
Family empowerment is a process or effort that aims to increase families' awareness of and willingness to care for their health. The purpose of this study was to determine, examine, and analyze family empowerment and the factors that inhibit it in patients with severe mental disorders in Banjarmasin City, Indonesia, in 2021. This study employed qualitative methods to elicit descriptive data in a written or spoken form from individuals and observed behavior to gain a better understanding of field phenomena through the collection of data or information obtained directly. At the Banjarmasin City Health Office, data were gathered through interviewing, documenting, and collecting secondary data. Interviews were conducted with key stakeholders, including families of patients with mental disorders, patients with mental disorders, and puskesmas mental health program management officers. The findings indicated that family empowerment was still suboptimal in patients with severe mental disorders; families lacked knowledge about caring for patients, impeding the healing process properly.